The role of parent-child relationship, school climate, happiness, and empathy to predict cyberbullying behavior - Triantoro Safaria; Hadi Suyono (International Journal of Evaluation and Research in Education (IJERE), 2020)
The lack of research on cyberbullying among Indonesian adolescents has become one of the critical arguments of this research. This study aimed to discover the factors that contribute to cyberbullying. This study took samples of students from three schools. The sample was 112 junior to senior high school students. The findings of this study indicate that school climate, parent-child relationship, and empathy have a significant role that encourages cyberbullying.